The relation of sexual function to migraine-related disability, depression and anxiety in patients with migraine - Eraslan, Defne; Dikmen, Pinar Yalinay; Aydinlar, Elif Ilgaz; Incesu, Cem (BMC, 2014)
Depression and anxiety are two phenomena that affect quality of life as well as sexual function. Depression and anxiety levels are reported to be high in migraine sufferers. We aimed to understand whether sexual function in women with migraine was associated to migraine-related disability and frequency of migraine attacks, and whether this relationship was modulated by depressive and anxiety symptoms. As migraine is more commonly seen in females, a total of 50 women with migraine were included. The diagnosis of migraine with or without aura was confirmed by two specialists in Neurology, according to the second edition of International Headache Society (IHS) International Classification of Headache Disorders (ICHD-II) in 2004. Migraine disability assessment scale score, female sexual function index scores, Beck depression inventory score and Beck anxiety inventory scores. Mean MIDAS score was 19.3 +/- 12.8, and mean number of migraine attacks per month were 4.3 +/- 2.7. Mean Female Sexual Function Index score was 20.9 +/- 5.9 and 90\% of patients had sexual dysfunction. Sexual dysfunction was not related to MIDAS score or frequency and severity of attacks. No relationship between sexual function and anxiety was found, whereas severity of depressive symptoms was closely related to sexual function. Depressive symptoms affected all dimensions of sexual function, except for pain. Sexual dysfunction seemed to be very common in our patients with migraine, while not related to migraine related disability, frequency of attacks and migraine severity or anxiety. The most important factor that predicted sexual function was depression, which was also independent of disease severity and migraine related disability. While future larger scale studies are needed to clarify the exact relationship, depressive and sexual problems should be properly addressed in all patients with migraine, regardless of disease severity or disability.
Keywords: Migraine; Sexual dysfunction; Migraine related disability; Depression; Anxiety